Age-specific mortality in Ukraine: an analytical examination of demographic development indicators - Yavorska, Viktoria; Melnyk, Nadiia; Melnyk, Andrii (Human Geography Journal, 2025)
Mortality as a key component of the natural population dynamics, serves not only as an indicator of a nation’s health status, but also s a reflection of deeper socio-economic, environmental and political processes in society. Particular attention is required by the analysis of changes in the pattern of mortality caused by long-term crisis phenomena, among them ‒ deterioration of living conditions, mass migration, war and consequent destruction of health infrastructure. The purpose of our scientific search is to estimate the age-specific mortality rate of population as a marker of structural features of mortality in Ukraine and its interpretation in the context of demographic development. In the course of the study, a quantitative–temporal analysis of age-specific mortality rates was employed. To interpret inter-age and gender variations in mortality rates, mathematical research methods were applied, while the spatial aspects of the distribution of age-specific mortality rates were examined using ranking techniques and cluster analysis. The age-specific mortality curves for both genders exhibit the classical J-shaped pattern, characterized by high mortality among infants, followed by a rapid decline that reaches its minimum in early childhood (around age five) and adolescence. Beginning from the 35+ age group, the curve rises exponentially, meaning that each subsequent age cohort faces a substantially higher risk of death than the preceding one—an increase described by the Gompertz law. During the studied period, we observe a decrease in the mortality rate in all age groups (after 2005), especially in childhood and adolescence, which indicates positive changes in access to medical services and the available medical infrastructure as a whole. The highest risks were recorded in persons of the 85+ age category. A sharp jump in mortality among the elderly is observed in 2020‒2021, which is obviously a consequence of the impact of the Covid 19 pandemic. An analysis of age-related mortality rates by gender revealed a significant excess of male mortality, especially at the age of 20‒60. The highest mortality rates were recorded in Kyiv, Zakarpattia, Kharkiv, Kherson and Chernivtsi regions, Kyiv. In general, the obtained data confirm that the mortality curve has a complex structure caused by a combination of biological, social and behavioral factors, and gender differences appear unevenly throughout the life cycle, reaching the greatest expressiveness in middle age and decreasing in the oldest groups.